Identities under construction: religion, gender, and sexuality among youth in Canada - Young, Pamela Dickey (Advancing studies in religion, 2020)
Introduction and Overview -- Emerging-Adult Religious and Sexual Experiences and Practices -- Emerging-Adult Opinions on Religion and Sexuality -- Forging Identities: The Influences of Parents, Peers, the Internet, and Religion -- Gender Experience and Opinion -- Negotiating Identities -- Emerging Adults and Unmarried Sex -- LGBTQI + Sexuality and Religion -- Religion in the World -- Conclusion.